High and Low Neurobehavior Disinhibition Clusters within Locales: Implications for Community Efforts to Prevent Substance Use Disorder. (May 2013) - Ridenour, Ty A.; Reynolds, Maureen; Ahlqvist, Ola; Zhai, Zu Wei; Kirisci, Levent; Vanyukov, Michael M.; Tarter, Ralph E.
<x xml:space="preserve">Abstract</x> Background: Knowledge of where substance use and other such behavioral problems frequently occur has aided policing, public health, and urban planning strategies to reduce such behaviors. Identifying locales characterized by high childhood neurobehavioral disinhibition (ND), a strong predictor of substance use and consequent disorder (SUD), may likewise improve prevention efforts. Objectives: The distribution of ND in 10–12-year olds was mapped to metropolitan Pittsburgh, PA, and tested for clustering within locales. Methods: The 738 participating families represented the population in terms of economic status, race, and population distribution. ND was measured using indicators of executive cognitive function, emotion regulation, and behavior control. Innovative geospatial analyzes statistically tested clustering of ND within locales while accounting for geographic barriers (large rivers, major highways), parental SUD severity, and neighborhood quality. Results: Clustering of youth with high and low ND occurred in specific locales. Accounting for geographic barriers better delineated where high ND is concentrated, areas which also tended to be characterized by greater parental SUD severity and poorer neighborhood quality. Conclusions and Significance: Offering programs that have been demonstrated to improve inhibitory control in locales where youth have high ND on average may reduce youth risk for SUD and other problem behaviors. As demonstrated by the present results, geospatial analysis of youth risk factors, frequently used in community coalition strategies, may be improved with greater statistical and measurement rigor.